Industrial gas piping system for chemical engineering laboratory Universiti Malaysia Pahang - Rosmimie, Abdullah (2013)
Industrial gas piping system for Faculty of Chemical and Natural Resources Engineering (FKKSA) laboratory is used to supply industrial gas to the equipments in clean room laboratory. The gases that are supplied to the laboratory are Nitrogen (N2), Carbon Dioxide (CO2), Oxygen (O2), Hydrogen (H2), Helium (He), Compressed Air, Nitrous Oxide (N2O), Acetylene (Ace) and Argon (Ar). These gases are used for specific equipment such as fermenter, gas chromatography (GC), and Atomic Absorption Spectroscopy (AAS).These equipments are used for research and training. The piping systems are generally stainless steel tubing with 3/8 inch and 1/4 inch tube outside diameters. There are five rooms in the cleanroom laboratory that involved with piping system, and they are BioTech Analytical Laboratory, BioTech Animal & Plant Cell Culture Room, BioTech Processing Scale Up Laboratory 1, BioTech Processing Scale Up Laboratory 2, Analytical Hot Laboratory, and Analytical Cool Laboratory. Generally, part of this piping system has already stopped from operating because of suspected leakage occurring in the system. This leakage can contribute to the economic loses as the gas escaped to the surrounding continuously. As small quantity of gases escape will greatly affect the cost (F. J. Callahan, 1993). There are cases where gases are supplied directly from cylinder to the equipment without a proper piping system. This is not complying with MS 830 clause 11.3 “the cylinder shall not be stored in a building or part thereof or structures attached thereto when the building is used as an educational institution”. The consequence from this non-compliance may cause the possibilities of inhaled gases by the public and lead to suffocation from the accumulation of flammable or reactive gases. In order to solve the problem, leak test should be conducted. However, this is not simple. It should be done with correct procedure by referring to appropriate standard. Similar goes to the cylinder storage area, it does not have enough signage as stated by MS 830 clause 10.7 “the messages in the form of signs shall be clearly displayed at the storage area”. The warning notice shall be in letters of at least 50mm high. Thus, this research is aim to identify the safety of the existing industrial gas piping system at selected laboratory and also to improve the existing system based on acceptable standards. Basically in this research, it involves site surveying, measurement, collecting data, discussion and documentation. Start with measuring the length of piping in selected room using measuring tape as the original drawing of the system was missing. Then, the drawing of the system is done by using AutoCAD. Next is to calculate the number of cylinder needed for the leak test for the piping system. After the calculation, the cost of leak test was estimated. Then, step by step procedure to conduct leak test are performed according to ASME B31.3. This procedure can be a reference to laboratory owners who want to conduct leak test in the future. The analysis of the safety in for the system is also carried out. From calculation, it shows that the volume of gas needed for test is 34281 ft3 at atmospheric pressure which is equal to 228 ft3 at 2200 psig. From this volume, supply pressure can be calculated and for all piping, the supply pressure calculated is generally higher than test pressure. Thus, only one cylinder is needed for all piping system. For safety analysis, it showed that eighteen items is complying with standards and ten items is not complying with the standards. This should be improved so that the system is safe to be used in the laboratory.